Diagnostic role of Golgi protein 73 and IL-17 in Egyptian cirrhotic rather than hepatocellular carcinoma patients - R. A. Nawaya, N. M. Abdel-Hamid, A. M. EL-Gayar, M. A. EL-Baiomy, N. M. El-Sherbiny, H. F. Ghazy (Journal of Applied Pharmaceutical Science, 2016)
Hepatocellular carcinoma (HCC) is the most common primary liver malignancy and the third cause of cancer mortality worldwide. This study aimed to pursue changes in serum interleukin-17 and Golgi protein 73 in both cirrhotic and HCC patients, as predictive tools for disease progression, cirrhosis was considered as the major risk prior to HCC. Fifty HCC patients were recruited from Mansura Oncology Center, Mansura University, Egypt, against 30 cirrhotic patients and 8 healthy subjects. Serum level of Golgi protein 73 was significantly increased in HCC and cirrhotic patients than control, but HCC group showed non-significant difference from cirrhotic group. Serum interleukin-17 increased significantly only in HCC patients. In HCC patients, a significant positive correlation was found between serum IL-17 to poor performance, presence of ascites, distant metastasis, portal vein thrombosis, Barcelona-Clinic Liver Cancer (BCLC) and Child scoring. IL-17 showed sensitivity of 54% and specificity of 60.5% in HCC patients, while AFP showed a sensitivity of 50% and specificity of 100%. IL-17 was positive in 48% of AFP-negative HCC patients. Combined determination of AFP and IL-17 had a sensitivity of 74% in HCC patients. Serum Golgi protein 73 is not a valuable diagnostic marker for HCC, serum IL-17 can be used as a better marker, related to HCC stages with poor prognostic criteria and metastasis. So it can be recommended as a new diagnostic marker. Combination of AFP and IL-17 increases the positive predictive value for HCC diagnosis and it is more helpful in diagnosing cirrhosis than HCC.
Keywords: HCC, Metastasis, AFP, GP-70, IL-17, Specificity, Sensitivity.